EFFECT OF DEXTRAN ON PLASMINOGEN ACTIVATOR INHIBITOR (PAI) - Saldeen, T; Moalli, R; Hasan, F M; Carvalho, A; Eriksson, M (Thrombosis and Haemostasis, 1987)
Adult respiratory distress syndrome (ARDS) is often associated with impaired fibrinolysis and appearance of microemboli in the lung. Increased production of PAI, associated with acute lung injury, may contribute to this process. In patients at risk of developing microembolic complications, aeteinistration of dextran reduced the incidence of ARDS. Accordingly, we studied the effect of dextran adninistration on plasma PAI levels in a rabbit model of endotoxin-induced lung injury and in patients. E coli endotoxin (500 μg/kg bw, infused over 5 min) was administrered to three groups of anesthetized, ventilated rabbits; 10 rabbits were pretreated and maintained with a 10% dextran-40 infusion (20 ml/kg bw), 6 received a 3% albunin solution (20 ml/kg bw) and 8 control rabbits received saline. Plasma PAI levels were measured by chrcmogenic assay. By 180 minutes after endotoxin infusion, PAI levels increased from 28 ± 6 to 155 ± 7 U/ml in the saline group, to 152 ± 10 U/ml in the albumin group and to 85 ± 8 U/ml in the dextran group.24 surgical patients were given 500 ml Dextran 70 (Macrodex) and PAI and t-PA were determined before, during and after dextran. PAI levels decreased 6 ± 8 U/ml during dextran infusion and 11 ±11 U/ml (26 per cent) after dextran, and was significantly decreased after correction for hemodilution. t-PA antigen levels were not changed due to dextran. Dextran thus has an effect on PAI levels which is not due to release of t-PA. Dextran by decreasing PAI levels may have unique salutary effects on fibrinolysis which may be important in the prevention of thrombotic disorders.